A Performance Analysis of Long-term Acute-Care Hospitals Owned by Large, Multistate Investor-Owned Companies. Issue 2 (April 2016) - Nayar, Preethy; Liu, Xinliang; McCue, Michael J.
Abstract : This study provides a descriptive assessment of the operating performance of for-profit long-term acute-care hospitals owned by multistate, investor-owned companies (large FP LTCHs) compared with FP LTCHs owned by smaller FP companies (small FP LTCHs) and nonprofit LTCHs (NP LTCHs). The study used the Centers for Medicare & Medicaid Services cost report data for 290 LTCHs from 2010 through 2012 to compare the financial performance of large and small FP LTCHs and NP LTCHs. The study found that the median operating profit margin for large FP LTCHs was 8.06%, which was twice as high as that of the small FP LTCHs and NP LTCHs (4.78% and 2.80%, respectively). Larger size, serving a greater proportion of private pay and more complex patients and incurring lower operating expenses, including salary expenses, may account for the higher operating margin of the large FP LTCHs.